Identifikasi Calon Petani Nilam Untuk Pengembangan Budidaya Nilam Berkelanjutan di Kabupaten Aceh Besar - Fadilla, Meutia; Putera, Muzakkir; Erwan, Friesca; Ulya, Zaudhatul; Sawitri, Yulia; Maizi, Hazful; Malahayati, Aisyah Juliawulan; Zulfan; Hifnalisa; Muhibbuddin (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2024)
The sustainable patchouli cultivation development program aims to promote community-driven agricultural practices through academic support from higher education institutions. Implemented in Teuladan Village, Aceh Besar Regency, the program utilizes the Triple Helix collaboration model, engaging academia, the community, and industry to ensure long-term sustainability. By employing a participatory approach, the initiative provides mentoring activities, including training on cultivation techniques, land management, and market dynamics for patchouli oil. Prospective farmers are selected through the CFCL (Candidate Farmers and Candidate Locations) questionnaire, which evaluates readiness based on skills, institutional organization, availability of extension workers, use of fuel for oil distillation, and commitment levels. The program aims to enhance farmers' knowledge and skills in producing high-quality patchouli, with a focus on Aceh Besar and extending across the Aceh region. By fostering sustainable agricultural practices and improving production quality, the initiative seeks to elevate community welfare and support the economic resilience of rural areas.